The Consecration of the Baptized and the Forgiveness of Original Sin in the Light of Saint Augustine - Castelló Gallo, Miguel Ángel (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2025)
Saint Augustine did not explicitly address the relationship between the consecration of the baptized and the forgiveness of original sin, but his writings suggest that both are facets of a single mystery. For the Bishop of Hippo, the reception of the sacrament, by visibly uniting the baptized with Christ, sanctifies his body, making it a member of Christ and a temple of the Holy Spirit. This consecration or sanctification of the body, wich is a pledge of resurrection, is only possible if the baptized person also visibily participates in the death of the Lord, through which original sin is forgiven. Just as union with Adam through physical generation causes humans to inherit sin, bodily union with Christ through visible baptism redeems them from it. Augustine understands consecration as a regeneration that cloth the baptized on the power of the Paschal Mystery, from which emerges the new man who will be fully realized in the resurrection.
Keywords: saint Augustine; baptism; original sin; baptismal dedication; character